2010 3rd International Conference on Computer Science and Information Technology 2010
DOI: 10.1109/iccsit.2010.5564010
|View full text |Cite
|
Sign up to set email alerts
|

Fast frequency sweep analysis of RCS by accelerated asymptotic waveform evaluation method

Abstract: The asymptotic waveform evaluation (AWE) technique is proposed with a preprocessing technique which is achieved by the arbitrarily dimensional fast lifting wavelet-like transform. With the new preprocessing technique, the sparse matrix equation in wavelet-domain is formed firstly. The wide band solution of this sparse linear system is obtained by application of AWE technique, and the actual induced surface current is computed by an inverse wavelet transform.Numerical simulation for differently shaped three dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Moment-matching ensures that the transfer functions of reduced and original models match at a single frequency of interest (Bai, 2002). Asymptotic waveform evaluation (AWE) is an explicit moment-matching method that has commonly been used in problem reduction of frequency domain electromagnetic analysis (Slone et al , 2003; Jiao and Jin, 1999; Chen et al , 2006, 2010). However, loss of accuracy occurs when simulating moment-matching reduced models over broad frequency ranges (Binion and Chen, 2009; Del Tin et al , 2006; Lienemann et al , 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moment-matching ensures that the transfer functions of reduced and original models match at a single frequency of interest (Bai, 2002). Asymptotic waveform evaluation (AWE) is an explicit moment-matching method that has commonly been used in problem reduction of frequency domain electromagnetic analysis (Slone et al , 2003; Jiao and Jin, 1999; Chen et al , 2006, 2010). However, loss of accuracy occurs when simulating moment-matching reduced models over broad frequency ranges (Binion and Chen, 2009; Del Tin et al , 2006; Lienemann et al , 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, loss of accuracy occurs when simulating moment-matching reduced models over broad frequency ranges (Binion and Chen, 2009; Del Tin et al , 2006; Lienemann et al , 2004). To address this, Slone et al (2003) used a multipoint Galerkin AWE method, where moments were matched at multiple frequencies; however, as pointed out by Chen et al (2010), AWE has been shown to be a numerically unstable process and computationally prohibitive with large original discretized models.…”
Section: Introductionmentioning
confidence: 99%